The Educational Signifi cance of Engagement with Diversity - Sardoč, Mitja (Two Homelands, 2012)
This article examines the issue of engagement with diversity and the various problems, tensions and challenges we are likely to encounter when including diversity in classrooms and other educational settings. The introductory section of this article deals with some preliminary considerations associated with the educational significance of engagement with diversity. I then introduce the three basic dimen- sions of diversity we are likely to encounter when discussing inclusion of diversity in any non-ideal educational environment. In Section III I examine the educational significance of engagement with diversity and identify the different functions engagement with diversity performs. In Section IV I examine the main controversies and the associated shortcomings any intuitive account of engagement with diver- sity is likely to face. In the conclusion, I specify how we should understand the idea of the fair treatment of engagement with diversity which is consistent with the commitment of educating students so as to recognise and respect one another as free and equal members of a polity.